Pengaruh Kualitas Pelayanan, Harga, Dan KepercayaanPada Jasa Pengiriman Jne Dan Tiki Terhadap LoyalitasKonsumen Online Shop (Studi Pada Mahasiswa Feb Ums) - Astuti, Alfiana Dwi, Farid Wajdi,Drs.,M.M.,Ph.D (2017)
This study aimed to analyzed the influence of service quality, price, and confidence in the consumer loyalty and Tiki JNE. This research is quantitative. Samples of this research is consumer customers and Tiki JNE Faculty of Economics and Business, University of Muhammadiyah Surakarta by 100 respondents with Sampling Quota sampling techniques. Methods of data collection using questionnaires. Data analysis techniques that test the validity, reliability testing, test analysis, T test, F test, and test the coefficient of determination (R2). Based on the calculation of the t test, F test showed that variables of service quality, price, and trust together with significant influence on consumer loyalty and Tiki JNE.